Study on eccentric compressive performance of circular double skin concrete filled steel tube connected by thread through inside lining tube - Ye Tianwen; Wang Qingli; Peng Kuan; Zhang Yijing (Scientific Reports)
Abstract Connection method of lengthening the steel tube of circular hollow sandwich concrete-filled steel tube by inside lining tube and thread is proposed. Twelve circular hollow sandwich concrete filled steel tubular beam-column connected by thread through inside lining tube are designed and fabricated using the length of the thread along the axial direction, the working height of the thread, and the position of the thread as parameters; In addition, one unconnected specimen and two welded specimens also are designed and fabricated to conduct controlled experimental research. The test phenomena and failure modes, axial compressive load-compression curve, axial compressive load-lateral deflection curve, and axial compressive load-strain in steel tube curve, as well as bearing capacity, strength reservation, deflection curve shape, lateral stiffness, ductility and plane section assumption are analyzed. The research results indicate that, within the parameter range studied, the thread connection through inside lining tube is reliable before tripping, and the experimental phenomenon of specimens connected by thread is basically consistent with that of the unconnected specimens. The axial compressive load-compression curve and axial compressive load-lateral deflection curve of all specimens can be approximately divided into elastic stage, elasto-plastic stage, and descending stage. The peak load of all specimens is relatively close, while although experiencing almost the same loading process, the strength reserve of the specimens connected by thread is insufficient. During the entire loading process, the shape of the deflection curve of all specimens is close to the sine half wave curve, and the distribution of longitudinal strain in the steel tube along the height of the middle cross-section basically conforms to the plane section assumption. Calculation method for bearing capacity of circular hollow sandwich concrete filled steel tubular beam-column connected by thread through inside lining tube is suggested.